2002
DOI: 10.1103/physrevlett.89.096802
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Current in Superconducting Nanorings

Abstract: The superconductivity in very thin rings is suppressed by quantum phase slips. As a result, the amplitude of the persistent current oscillations with flux becomes exponentially small, and their shape changes from sawtooth to a sinusoidal one. We reduce the problem of low-energy properties of a superconducting nanoring to that of a quantum particle in a sinusoidal potential and show that the dependence of the current on the flux belongs to a one-parameter family of functions obtained by solving the respective S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
294
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(306 citation statements)
references
References 14 publications
12
294
0
Order By: Relevance
“…The only source of coupling between different rhombi is the periodic boundary condition along the chain. The method to treat similar problem was developed recently by Matveev, Larkin and Glazman [5] (MLG). They considered simple chain of N Josephson junctions in the closed-ring geometry, and reduced calculation of supercurrent in large-N limit to the solution of a Schröedinger equation for a particle moving in a periodic potential ∼ cos x, with appropriate boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…The only source of coupling between different rhombi is the periodic boundary condition along the chain. The method to treat similar problem was developed recently by Matveev, Larkin and Glazman [5] (MLG). They considered simple chain of N Josephson junctions in the closed-ring geometry, and reduced calculation of supercurrent in large-N limit to the solution of a Schröedinger equation for a particle moving in a periodic potential ∼ cos x, with appropriate boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum phase slips (QPS) in the junctions can be viewed as the charge-sensitive fluxon tunneling [9,10] provided the conditions discussed below are satisfied. Microwave experiments [11] have demonstrated that dephasing of a fluxonium, a small Josephson junction shunted by a 1D Josephson chain, can be due to the effect of fluctuating charges on the QPS in the chain.…”
mentioning
confidence: 99%
“…The allowed states of a superconducting ring differ by the phase change accumulated over the circumference of the loop. The energy of the n-th state is given by [6]:…”
mentioning
confidence: 99%